2011
DOI: 10.1080/10810730.2010.546491
|View full text |Cite
|
Sign up to set email alerts
|

Including Limitations in News Coverage of Cancer Research: Effects of News Hedging on Fatalism, Medical Skepticism, Patient Trust, and Backlash

Abstract: Past research has demonstrated that news coverage of cancer research, and scientific research generally, rarely contains discourse-based hedging, including caveats, limitations, and uncertainties. In a multiple message experiment (k = 4 news stories, N = 1082), the authors examined whether hedging shaped the perceptions of news consumers. The results revealed that participants were significantly less fatalistic about cancer (p = .039) and marginally less prone to nutritional backlash (p = .056) after exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 57 publications
5
85
4
1
Order By: Relevance
“…Local TV cancer news, on average, lasted less than one minute (i.e., 45.25 seconds vs. national TV’s 1 min 20.24 seconds); thus, local TV news viewers may be less likely than national TV news viewers to gain health or cancer knowledge from their exposure to local TV news coverage. Considering that health knowledge and health literacy are negatively associated with problematic perceptions about cancer (e.g., fatalism, overload; Jensen et al, 2011; Lee, Niederdeppe, & Freres, 2012) and are likely to promote health-enhancing behaviors (e.g., healthy lifestyle and disease-screening behaviors; Hornik et al, in press; Lee, 2009), health educators and public health practitioners may not be able to rely upon local TV cancer news as their major information channel to convey cancer-related information to the public. Short cancer stories are also problematic because they are less likely than longer stories to include follow-up information, which allows viewers to evaluate the credibility of cancer stories by identifying source materials behind those stories and seeking relevant further information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local TV cancer news, on average, lasted less than one minute (i.e., 45.25 seconds vs. national TV’s 1 min 20.24 seconds); thus, local TV news viewers may be less likely than national TV news viewers to gain health or cancer knowledge from their exposure to local TV news coverage. Considering that health knowledge and health literacy are negatively associated with problematic perceptions about cancer (e.g., fatalism, overload; Jensen et al, 2011; Lee, Niederdeppe, & Freres, 2012) and are likely to promote health-enhancing behaviors (e.g., healthy lifestyle and disease-screening behaviors; Hornik et al, in press; Lee, 2009), health educators and public health practitioners may not be able to rely upon local TV cancer news as their major information channel to convey cancer-related information to the public. Short cancer stories are also problematic because they are less likely than longer stories to include follow-up information, which allows viewers to evaluate the credibility of cancer stories by identifying source materials behind those stories and seeking relevant further information.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while this study revealed some differences between how local TV news and national TV news cover cancer, future studies should investigate differences between national and local TV news coverage of cancer in greater detail. For instance, we suggest that the following questions should be addressed: Are local TV news stories more likely than national TV news to convey cancer-related research findings without appropriate caveats and hedges (e.g., Jensen et al, 2011)? Does local TV news coverage report new, controversial causes of cancer more often than national TV news coverage (e.g., Nelkin, 1995; Stocking, 1999)?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hedging and two-sided information are important when covering health findings, but they also may trigger uncertainty and disorientation. Jensen and colleagues consistently have explored audience responses to health news that features hedging (Jensen, 2008;Jensen et al, 2011), but it is not clear how people respond to two-sided conflicting news. The current article has investigated this question by proposing a moderated mediation model to explore audience responses to such coverage.…”
Section: Findings and Contributionsmentioning
confidence: 97%
“…These fatalistic beliefs might result from media coverage, through their tone and focus (Jensen et al, 2011; McClure, Allen, & Walkey, 2001; Niederdeppe, Fowler, Goldstein, & Pribble, 2010). Rather than discussing all aspects of the disease—including risk factors, prevention, treatment, and outcomes—a focus in simplified news stories mainly on the causes of cancer makes these causes more salient to the determinant of other important factors about cancer, namely prevention (Slater, Hayes, Reineke, Long, & Bettinghaus, 2008).…”
mentioning
confidence: 99%